The Role Of Risk Management In Improving Company Financial Stability In The Digital Era - Supena Supena; Asep Sugito (Pascasarjana STIE Miftahul Huda, 2025)
Digital transformation has significantly impacted the way companies operate, while expanding the spectrum of risks they face. This study aims to explore the role of risk management in strengthening corporate financial stability in the digital era. The methodology used is a descriptive-qualitative approach by conducting a literature review from various primary and secondary sources. The research findings indicate that the implementation of structured and integrated risk management can increase corporate financial resilience to external disruptions, such as cyber threats, market fluctuations, and uncertainty in digital regulations. In conclusion, risk management serves as a strategic element in maintaining business continuity and increasing stakeholder trust. Keywords: risk management, financial stability, digital transformation, companies, business resilience.